Investigating Interrogation System In Gregor Jordan's Unthinkable Movie (2010): A Humanistic Approach - VALENSIA, FADHOLY PRASTIKA PANDU (2012)
The major problems of this study are how the major character keeps on his principle and how the violation happens to the major character? The objectives of the study are: to describe the reasons why the major character keeps on his principle and to describe how the police' behavior in violating the major character, and also why it is not suitable with the human being. In conducting this study, the researcher uses qualitative research in which the data are based on primary data source, the movie Gregor Jordan's Unthinkable itself. The secondary data are other data which deal with the research. In analysing the data, he applies two analysis, firtsly, structural approach which is used to analyze the elements of the movie. It consists of two elements of movie; they are narrative elements and technical elements. Secondly, the humanistic approach is used for analysing interrogation system applied by police and characteristics of Younger. In conclusion, the writer finds that the narrative elements of movie consist of characters and characterization, setting plot, point of view and theme. The technical elements consist of mise-en-scene, cinematography, sound and editing. In humanistic analysis, the writer concludes that interrogation system which is applied by police is contradicted with human being. As human being Younger has many needs to fulfill his life. Younger has been treated badly, but it cannot stop Younger to keep in silent.